An analysis on students' thesis topics and research types in automotive engineering education program - Ibnu Siswanto; Hongbo Ma; Sigit Kurniawan (Jurnal Pendidikan Vokasi, 2022)
This study aims to analyze the topics and types/methods of research in the thesis of students of the Automotive Engineering Education study program, Universitas Negeri Yogyakarta. This research is descriptive research. The types/methods were descriptive models, Action Research, Ex Post-Facto, Research and Development, Evaluation, and Experimental Research (100, 69, 50, 35, 30, and 23 studies respectively). The study was conducted by analyzing 320 student thesis articles published from 2014 to 2018 in the Yogyakarta State University student e-journal. The results showed that the student's thesis topics consisted of 5 research topics, namely: education (139 topics), learning (120 topics), media development (43 topics), university issues (9 topics), and automotive engineering topics (9 pieces). Based on the results of the research, the types/research methods used were categorized into six methods, namely descriptive models (100 studies), classroom action research (69 studies), ex-post-facto (50 studies), research and development (48 studies), evaluation (30 studies), research and experimental (23 studies).